2011
DOI: 10.1007/s11250-011-0036-6
|View full text |Cite|
|
Sign up to set email alerts
|

Estimates of phenotypic and genetic parameters for birth weight of Brown Swiss calves in Turkey using an animal model

Abstract: A study was conducted to assess the influence of genetic and environmental factors on Brown Swiss calf birth weight, and to estimate variance components, genetic parameters, and breeding values. Data were collected on 1,761 Brown Swiss calves born from 1990 to 2005 in the Konuklar State Farm in Turkey. Mean birth weight for all calves was 39.3 ± 0.09 kg. Least squares mean birth weights for male and female Brown Swiss calves were 40.3 ± 0.02 and 39.0 ± 0.02 kg, respectively. Variance components, genetic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In the study of Demeke and Neser Schoeman (2003), a small (yet non-zero) estimate was also reported for maternal heritability for BW. This finding was similar to those in the study of Sahin et al (2012). Pico (2004) and Plasse et al (2002aPlasse et al ( , 2002b previously informed m 2 for BW values of 0.11, 0.08 and 0.07 in Brahman cattle; these values are lower than the ones identified in the current study.…”
Section: Heritabilitiessupporting
confidence: 93%
See 3 more Smart Citations
“…In the study of Demeke and Neser Schoeman (2003), a small (yet non-zero) estimate was also reported for maternal heritability for BW. This finding was similar to those in the study of Sahin et al (2012). Pico (2004) and Plasse et al (2002aPlasse et al ( , 2002b previously informed m 2 for BW values of 0.11, 0.08 and 0.07 in Brahman cattle; these values are lower than the ones identified in the current study.…”
Section: Heritabilitiessupporting
confidence: 93%
“…The r am was negative and high for models 4 (−0.76 ± 0.027) and 6 (−0.67 ± 0.115). Similarly, genetic correlations estimated by Sahin et al (2012) for Brown Swiss calves, Karabulut et al (2012) for Holstein calves were negative and ranged from −0.58 to −1.00. However, compared to the results of the current study, lower r am estimates (−0.35 to −0.37) have been informed for Brahman cattle (Plasse et al 2002a;Pico 2004), while similar estimates have been noticed for Nellore cattle (−0.72, Eler et al 1995) and Boran cattle (−0.55, Haile-Mariam & Kassa-Mersha 1995).…”
Section: Genetic Correlations and Covariancesmentioning
confidence: 87%
See 2 more Smart Citations
“…The genetic light of birth weight in farm animals indicated that it consider as the most important character influences the lifetime yields of the animal (Karakus et al, 2010). On the basis of this knowledge genetic improvement programs must be introduce the birth weight for its easily measur in one hand and its correlation with of other beef performance traits in the other hand (Sahin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%